APPLICATION OF ZEOLITE AT SANDY SOIL FOR SEEDLINGS MEDIA OF OIL PALM - S. Rahutomo; Winarna Winarna; H. Santoso; E. S. Sutarta (Jurnal Zeolit Indonesia, 2010)
Two studies of zeolite application on oil palm seedlings for repair media of planting using a sandy soil type to seedlings media of oil palm have been conducted by The Oil Palm Research Center at experimental garden Aek Pancur, North Sumatra. Research I using Typic Udipsamment soil with 4 dose level of zeolite (0,50,100, and 150 g / polybag). Research II using tin tailings which treated zeolite soil amelioran materials, empty fruit bunch compost, dolomite, and also compared with the top soil is Typic Hapludult. The study I showed that application of zeolite is generally able to increase nutrient content in soil and soil cation exchange capacity inclined growth of better seeds. However, at doses of 150 g/polybag, zeolite application actually lowers the pH and increasing Aldd was followed by poor seedling growth. The study II using tin tailings as planting media, zeolite application has not yielded as good as empty fruit bunch compost applications to support seedling growth and nutrient uptake. Continued research related to determining the appropriate dose, and combination with other soil amelioran materials to increasing effectiveness of zeolite in improving the physical, chemical, and biological soil charachteristic as a medium sand fraction dominated planting of oil palm breeding is still very necessary.